An Update of the Role of Renin Angiotensin in Cardiovascular Homeostasis. (February 2015) - Farag, Ehab; Maheshwari, Kamal; Morgan, Joseph; Sakr Esa, Wael Ali; Doyle, D. John
<x xml:space="preserve">Abstract</x> The renin angiotensin system (RAS) is thought to be the body's main vasoconstrictor system, with physiological effects mediated via the interaction of angiotensin II with angiotensin I receptors (the "classic" RAS model). However, since the discovery of the heptapeptide angiotensin 1–7 and the development of the concept of the "alternate" RAS system, with its ability to reduce arterial blood pressure, our understanding of this physiologic system has changed dramatically. In this review, we focus on the newly discovered functions of the RAS, particularly the potential clinical significance of these developments, especially in the realm of new pharmacologic interventions for treating cardiovascular disease.